Effectiveness of Mobile Geriatrics Clinic Program to Reduce Crowding of Secondary Hospitals - Asavatanabodee, Paibool (Journal of Health Science of Thailand, 2019)
Currently, government hospitals have encountered a large number of patients. To address such situation, Mahasarakham Hospital has set up a “Mobile Geriatrics Clinic” to provide services for the elderly in Mueang Maha Sarakham District who have knee problems, risk of falls, abnormal vision, psychiatrics problem, poor diabetes or high blood pressure. The service activities including eye screening, reducing knee pain, assessing the risk of falls, providing nutrition knowledge, exercise and physical therapy that suited for the elderly and osteoarthritis patients. There is a medical examination by the doctor and assess mental status and follow-up visit to the elderly at home. Mobile Geriatrics Clinic, which is a unit that extends the services of primary care to be more proactive to reduce crowding in the hospitals. The objectives of this study were to assess effectiveness of the mobile geriatrics clinic and to develop a suitable mobile service model to accommodate high number of the elderly in the future. The effectiveness study was conducted by comparing the number of hospital visits to the outpatient department due to diabetes, hypertension psychiatric diseases and bone and joint diseases before and after the establishment of the mobile clinic. Data on the causes affecting elderly health were collected by focus group discussion with elderly people who participated in the project. Paired t-test statistics was used for the comparison. It was found that there were 180 patients attending the elderly clinic. The average age of the patients was 71.98±6.95 years old. After operating the Mobile Geriatrics Clinic, the average number of OPD visits decreased by 2.285 times (p<0.01). The average number of OPD visits with diabetes, hypertension, psychiatric disease and falls significantly decreased by 1.173 times (p<0.01). Thus, the Mobile Geriatrics Clinic could reduce congestion of the hospital. In addition, increased access to primary care services and improve health and quality of life of the elderly and their caregivers. Ministry of Public Health should develop a policy to apply this approach in other secondary and community hospitals.